2020
DOI: 10.3390/ijerph17228538
|View full text |Cite
|
Sign up to set email alerts
|

Key Determinants of Anemia among Youngsters under Five Years in Senegal, Malawi, and Angola

Abstract: Anemia is characterized as a condition where there is a deficient number of hematocrit, hemoglobin, or red cells in the human body. This condition affects most youngsters under five years old and pregnant women. The fundamental goal of this paper is to investigate anemia, recognize its determinants, and propose critical proposals to achieve 2030 Sustainable Development Goal with a focus on Senegal, Malawi, and Angola. This research utilized 2016 nationally representative information from Senegal, Malawi, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Anaemic children from the poorest, poorer and middle household wealth index had a high probability of being moderately anaemic compared to children from the richest households. This nding is supported by the ndings of other studies in sub-Saharan Africa [16,22,25,[34][35][36][49][50][51][52][53][54]. The predominant explanation is that richer households can afford good quality healthcare services, live under proper sanitary conditions, consume more nutritious foods and are food secured.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Anaemic children from the poorest, poorer and middle household wealth index had a high probability of being moderately anaemic compared to children from the richest households. This nding is supported by the ndings of other studies in sub-Saharan Africa [16,22,25,[34][35][36][49][50][51][52][53][54]. The predominant explanation is that richer households can afford good quality healthcare services, live under proper sanitary conditions, consume more nutritious foods and are food secured.…”
Section: Discussionsupporting
confidence: 57%
“…Other studies conducted within the African region found similar anaemia levels among children aged 6-59 months using nationally representative data [18, [34][35][36].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Based on a review of the literature (Khulu & Ramroop, 2020 ; Moschovis et al, 2018 ), information available in the DHS data set and the use of a directed acyclic graph, we considered the following as potential confounders: year of the survey, wealth index quintile, place of residence (urban, rural), living with a partner (yes, no) and woman's age (continuous). Conceptually, potential confounders were associated with both women's empowerment and anaemia but not on the causal pathway between these two variables.…”
Section: Methodsmentioning
confidence: 99%
“…Anaemia in Malawi, Senegal, and Angola was revealed to be associated with household wealth status, the mother’s level of schooling, and the age of the child, whereas, malnutrition was found to be associated with the type of residence, mother’s level of schooling, household wealth status, and child’s age [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%